Antifungal activity of algal extracts against plant pathogenic fungi - Kamble, S M; Rokde, A U; Chavan, Ashok M (International Multidisciplinary Research Journal, 2012)
Extracts of different algal samples were tested for different fungal population; it reveals thatÂ cold water extract of algae showed antifungal activity.